MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IVB SDN 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - Asriati ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
Based on the experience of researchers teach in class IV student learning outcomes IPS Class IVB SDN 011 Bukit Gajah Kecamatan Ukui Kabupaten Pelalawan. In SDN 011 Bukit Gajah Kecamatan Ukui Kabupaten Pelalawan that the results of learning IPS as expected has not been achieved in accordance with the standards of completeness, Of KKM has been determined that 70, only about 12 students who were able to transcend the KKM and the remaining 10 students have not been able to achieve a predetermined KKM. In this regard, we need a method of learning that is able to facilitate students to gain experience of learning so as to provide greater opportunities for students to be able to develop in accordance with the wishes and abilities. The purpose of this research is to improve student learning outcomes IPS SDN 011 Class IVB SDN 011 Bukit Gajah Kecamatan Ukui Kabupaten Pelalawan by implementing cooperative learning model numbered heads together (NHT). This research forms a classroom action research (PTK). From the research data is a daily test results of students from elementary to UH I score has risen from an average of 60.78 into 77.5 18.09%. IPS learning outcome from the base score to UH II also increased, namely from 60.78 into 83.28 by 37.02% and the teacher's activities each meeting has increased. From the first meeting in the first cycle of the activities of teachers percentage is 58.33% increased in the second cycle at the last meeting be 87.5%. Activities of students each meeting also increased. In the first cycle of the first meeting of student activity percentage was 58.33% and increased in the second cycle last meeting to 83.33.